Interventoría a planes de manejo ambiental con aplicación práctica al proyecto distrito de riego triángulo del Tolima-componente captación-bocatoma ﻿ (2012)
The project seeks to develop and implement a model to follow, for the auditing of Environmental Management Plans (EMPs) by control records that allow to generate quantitative and qualitative monitoring indicators of the tasks performed by the contractor in the execution of the work. It is necessary to have a verification methodology in field, of the activities outlined in the Environmental Management Planexecuted by the contractor, to performauditing to the same; this will facilitate the work follow-up to the auditor, accompanied with the revision of all documentary information provided by the contractor (monitoring results, laboratory results, tax payments for using of natural resources, certificates of hazardous solid waste disposal etc.) Environmental monitoring records are applied to the Irrigation District Triángulodel Tolimacatchment component; such registration has abase reportanda photographic recordof the activities carried out during the period; this is the support of the activities reported. The former shows that the record includes the oretical and practical information to be run by the contractor, which is reflected in the score obtained in each one of the logs. This record also allows the auditor to contrast in the work, information provided by the contractor like: monitoring results, agreements with communities, and other documents that are rooted to the audit. The implementation of the environmental monitoring record allows to detect in a quickly and argumented way, the EM Plogs that presenta low percentage of compliance, as well as the ones in which environmental measures applied by the contractor present a high percentage